Behavior and quantitative characterization of CBN wheel wear in high-speed grinding of nickel-based superalloy. Issue 9 (December 2016) - Zhao, Zhengcai; Fu, Yucan; Xu, Jiuhua; Zhang, Zhiwei
Abstract This work aims to clarify the wear behavior and quantitatively characterize the wear in cubic boron nitride (CBN) wheels during the high-speed grinding of the nickel alloy, Inconel 718. Grinding experiments were performed first to qualitatively investigate the wear behavior of CBN wheels. To simplify the grinding process, single-grit grinding experiments were carried out to quantitatively characterize the degree of wear on the CBN grain afterwards. The influence of maximum chip thickness on the wear and grinding ratio of CBN grains was studied. Finally, the wear of the CBN wheel was quantitatively characterized by using the wear flat area percentage. It was found that the wear of a single CBN grain increases dramatically at first and then varies little with the increase in the accumulated material removal. The wear flat area percentage of the CBN grinding wheel is able to remain at a low level, and a high and stable grinding ratio can be achieved for CBN wheels. This demonstrates the feasibility of CBN wheels in the high-speed grinding of nickel alloys.